Investigating Multidimensional Interoceptive Awareness in a Japanese Population: Validation of the Japanese MAIA-J - Shoji, Masayasu; Mehling, Wolf E.; Hautzinger, Martin; Herbert, Beate M. (Frontiers in Psychology, 2018)
The Multidimensional Assessment of Interoceptive Awareness (MAIA) is a self-report instrument to assess relevant dimensions of bodily awareness. The aim of this study was to offer a Japanese version and adaptation of the MAIA (MAIA-J), as well as to analyse its psychometric properties in a Japanese population. The English MAIA was systematically forward and backward translated by bi-lingual Japanese experts; additionally, content validity aspects regarding language were discussed by a panel of experts. The MAIA-J was administered to 390 Japanese young adults (age: 20.3 ± 2.2), 67.7% women and 32.2% men. Exploratory factor analysis (EFA) reduced the questionnaire from 32 to 25 items and from 8 to 6 factors (Noticing, Not-Distracting, Attention Regulation, Emotional Awareness, Body Listening, and Trusting). The Japanese version showed appropriate indicators of construct validity and reliability, with Cronbach's α between 0.67 and 0.87 for the 6 MAIA-J dimensions. The findings demonstrate that MAIA-J has a slightly different factor structure compared to the original English MAIA. Results are discussed with respect to cultural differences. However, the study results support acceptable reliability of the MAIA-J in the Japanese sample, warranting its use for future studies with Japanese populations.